A high-strength flame-retardant bus duct and preparation method thereof
By combining modified zirconium diboride material with epoxy resin, the lack of strength and flame retardancy of busbar troughs is solved, and higher strength and flame retardant performance is achieved, meeting the electricity demand of modern high-charge buildings .
Patent Information
- Application Number
- CN202410638522.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-05-22
AI Technical Summary
The existing bus ducts on the market cannot meet the power requirements of modern high-rise buildings and large factories in terms of strength and flame retardancy. Traditional fillers have poor compatibility with resins and limited performance improvement.
Modified zirconium diboride material as high-strength flame retardant filler, combined with epoxy resin through chemical click reaction, prepare cast resin with high strength and flame retardant properties, and apply it to the busbar trough through specific process steps. Protective layer.
It significantly improves the strength, toughness and flame retardant performance of the bus duct, ensuring higher safety and reliability.
Abstract
Description
Technical Field
[0001] The invention relates to the field of bus ducts, and in particular to a high-strength flame-retardant bus duct and a preparation method thereof. Background Art
[0002] With the rapid development of cities, the electricity load of buildings has increased dramatically. The original wires and cables have been gradually replaced by bus ducts with large capacity and convenient branching and bundling management due to the inconvenience of branching and bundling management. Bus duct is a closed metal device composed of copper and aluminum busbars, which is used to distribute high power to various components of the distributed system. Composite multifunctional bus ducts are widely used in power transmission trunks for fire fighting equipment and fire emergency equipment trunks.
[0003] With the emergence of modern engineering facilities and equipment, the electricity consumption of all walks of life has increased rapidly, especially with the emergence of numerous high-rise buildings and large workshops. Traditional cables as transmission conductors can no longer meet the requirements in high-current transmission systems. The parallel use of multiple cables has brought many inconveniences to on-site installation and construction. Plug-in bus ducts have emerged as a new type of distribution conductor. Compared with traditional cables, they fully demonstrate their superiority in high-current transmission. At the same time, due to the use of new technologies and new processes, the contact resistance and temperature rise of the connection points at both ends of the bus duct and the plug-in points of the branch ports are greatly reduced. High-quality insulating materials are used in the bus duct, thereby improving the safety and reliability of the bus duct and making the entire system more perfect.
[0004] Currently, most of the cast bus ducts on the market are cast with high-performance insulating resin and inorganic minerals. The busbars are directly cast and sealed. They have certain strength, fire resistance, explosion-proof and other functions. However, with the increasing requirements for bus ducts, the strength and flame retardancy of the bus ducts currently on the market can no longer meet the demand. Summary of the invention
[0005] In view of the problems existing in the prior art, an object of the present invention is to provide a high-strength flame-retardant bus duct and a preparation method thereof.
[0006] The purpose of the present invention is achieved by the following technical solutions:
[0007] In a first aspect, the present invention provides a high-strength flame-retardant bus duct, comprising a bus and a protective layer arranged on the surface of the bus, wherein the protective layer is prepared by casting resin, and the casting resin is calculated by weight and comprises:
[0008] 100 parts of epoxy resin, 18-42 parts of high-strength flame retardant filler, 0.5-1 parts of defoamer, 1-3 parts of lubricant and 20-40 parts of curing agent.
[0009] Preferably, the epoxy resin is one or more combinations of epoxy resin E-12, epoxy resin E-20, epoxy resin E-44, and epoxy resin E-51; more preferably, the epoxy resin is epoxy resin E-51.
[0010] Preferably, the high-strength flame-retardant filler is a modified zirconium diboride material, which is prepared by a chemical click reaction using 4-hydroxythiophenol and double-bond functionalized zirconium diboride as raw materials.
[0011] Preferably, the defoamer is an organosilicon defoamer, including any one or more of BYK-024, BYK-093, BYK-A530, and BYK-141.
[0012] Preferably, the lubricant is a mixture of one or more of stearic acid, zinc stearate and magnesium stearate.
[0013] Preferably, the curing agent is an acid anhydride curing agent, including a mixture of one or more of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, nadic anhydride, and methylnadic anhydride.
[0014] Preferably, the preparation method of the modified zirconium diboride material comprises:
[0015] S1. Weigh zirconium diboride ceramic powder and anhydrous ethanol, mix them, then add vinyl silane coupling agent, disperse them evenly under the action of ultrasound, and then reflux and stir them under the protection of nitrogen. After the treatment, filter and collect solid particles, wash them three times with water, and vacuum dry them to obtain double-bond functionalized zirconium diboride;
[0016] S2. Weigh 4-hydroxythiophenol and double-bond functionalized zirconium diboride and add them to N-methylpyrrolidone in sequence. After stirring until uniform, add a photoinitiator. Under the irradiation of ultraviolet light, continue stirring to react. After the reaction is completed, filter and collect solid particles, wash three times with alcohol, and vacuum dry to obtain a modified zirconium diboride material.
[0017] More preferably, in said S1, the particle size of the zirconium diboride ceramic powder is 600-800 mesh.
[0018] More preferably, in S1, the vinyl silane coupling agent is A-151 or A-172, and the added amount is 16%-28% of the mass of the zirconium diboride ceramic powder.
[0019] More preferably, in S1, the mass volume ratio of zirconium diboride ceramic powder and anhydrous ethanol is 1 g: (10-20) mL.
[0020] More preferably, in said S1, the treatment temperature is 60-70°C, and the treatment time is 10-15h.
[0021] More preferably, in S2, the mass volume ratio of 4-hydroxythiophenol, double-bond functionalized zirconium diboride, and N-methylpyrrolidone is (0.26-0.52) g: 1 g: (10-20) mL.
[0022] More preferably, in S2, the photoinitiator is benzophenone, and the added amount is 2%-6% of the mass of 4-hydroxythiophenol.
[0023] More preferably, in S2, the wavelength of the ultraviolet lamp is 365nm, the power is 500W, and the irradiation time is 20-60min.
[0024] In a second aspect, the present invention provides a method for preparing a high-strength flame-retardant bus duct, comprising the following steps:
[0025] The first step is to weigh epoxy resin, high-strength flame retardant filler, defoamer, and lubricant according to weight parts, mix them evenly, add curing agent, mix them evenly again, and obtain casting resin;
[0026] The second step is to place the busbar in the mold, then pour in the casting resin, vibrate and degas, heat the mold to 130-150℃ for 2-4h, and then naturally cool it and demould it to obtain a high-strength flame-retardant busbar duct.
[0027] The beneficial effects of the present invention are:
[0028] 1. The present invention prepares a casting resin for a bus duct, using epoxy resin as the main raw material, adding high-strength flame-retardant filler, and further adding auxiliary agents and curing agents. The prepared casting resin has higher strength and toughness than conventional resins, and also has a certain flame-retardant effect.
[0029] 2. The present invention improves the filler. Traditional fillers are basically inorganic materials, which not only have poor compatibility with resins, but also have limited performance improvement on resins. The present invention uses zirconium diboride ceramic material as a base material, first treats its surface with a vinyl silane coupling agent to functionalize its surface double bonds, and then combines it with 4-hydroxythiophenol. The double bond-thiol group undergoes a click chemical reaction under photocatalysis, thereby obtaining a coated modified zirconium diboride material.
[0030] 3. The surface of the modified zirconium diboride material prepared by the present invention is rich in phenolic hydroxyl groups and sulfide groups, and has high strength and thermal stability. On the one hand, it greatly improves the flame retardant performance of the filler, and on the other hand, it has good bonding with the epoxy resin and can also improve the performance of the epoxy resin. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.
[0032] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0033] The present invention will be further described below in conjunction with the following examples.
[0034] Example 1
[0035] A high-strength flame-retardant bus duct comprises a bus and a protective layer arranged on the surface of the bus, wherein the protective layer is prepared by casting resin, and the casting resin is calculated by weight and comprises:
[0036] 100 parts of epoxy resin, 30 parts of high-strength flame retardant filler, 0.6 parts of defoamer, 2 parts of lubricant and 30 parts of curing agent.
[0037] The epoxy resin is epoxy resin E-51, the defoamer is silicone defoamer BYK-024, the lubricant is zinc stearate, and the curing agent is anhydride curing agent nadic anhydride.
[0038] Wherein, the preparation method of the modified zirconium diboride material comprises:
[0039] S1. Weigh 600-800 mesh zirconium diboride ceramic powder and anhydrous ethanol, mix them, the mass volume ratio of zirconium diboride ceramic powder and anhydrous ethanol is 1g:15mL, then add vinyl silane coupling agent A-151, the addition amount is 22% of the mass of zirconium diboride ceramic powder, disperse them evenly under the action of ultrasound, then reflux and stir at 65°C for 12h under the protection of nitrogen, after the treatment, filter and collect solid particles, wash them three times with water, and vacuum dry them to obtain double-bond functionalized zirconium diboride;
[0040] S2. Weigh 4-hydroxythiophenol and double-bond functionalized zirconium diboride and add them to N-methylpyrrolidone in sequence. The mass volume ratio of 4-hydroxythiophenol, double-bond functionalized zirconium diboride and N-methylpyrrolidone is 0.39g:1g:15mL. After stirring until uniform, add photoinitiator benzophenone in an amount of 4% of the mass of 4-hydroxythiophenol. Irradiate with an ultraviolet lamp with a wavelength of 365nm and a power of 500W for 40min. Continue stirring to react. After the reaction is completed, filter and collect solid particles, wash three times with alcohol, and vacuum dry to obtain a modified zirconium diboride material.
[0041] The method for preparing the high-strength flame-retardant bus duct comprises the following steps:
[0042] The first step is to weigh epoxy resin, high-strength flame retardant filler, defoamer, and lubricant according to weight parts, mix them evenly, add curing agent, mix them evenly again, and obtain casting resin;
[0043] The second step is to place the busbar in the mold, then pour in the casting resin, vibrate and degas, heat the mold to 145°C for 3 hours, and then naturally cool it and demold it to obtain a high-strength flame-retardant busbar duct.
[0044] Example 2
[0045] A high-strength flame-retardant bus duct comprises a bus and a protective layer arranged on the surface of the bus, wherein the protective layer is prepared by casting resin, and the casting resin is calculated by weight and comprises:
[0046] 100 parts of epoxy resin, 18 parts of high-strength flame retardant filler, 0.5 parts of defoamer, 1 part of lubricant and 20 parts of curing agent.
[0047] Wherein, the epoxy resin is epoxy resin E-20, the defoamer is silicone defoamer BYK-093, the lubricant is magnesium stearate, and the curing agent is anhydride curing agent methyl hexahydrophthalic anhydride.
[0048] Wherein, the preparation method of the modified zirconium diboride material comprises:
[0049] S1. Weigh 600-800 mesh zirconium diboride ceramic powder and anhydrous ethanol, mix them, the mass volume ratio of zirconium diboride ceramic powder and anhydrous ethanol is 1g:10mL, then add vinyl silane coupling agent A-172, the addition amount is 16% of the mass of zirconium diboride ceramic powder, disperse them evenly under the action of ultrasound, then reflux and stir at 60°C for 10h under the protection of nitrogen, after the treatment, filter and collect solid particles, wash them three times with water, and vacuum dry them to obtain double-bond functionalized zirconium diboride;
[0050] S2. Weigh 4-hydroxythiophenol and double-bond functionalized zirconium diboride and add them to N-methylpyrrolidone in sequence. The mass volume ratio of 4-hydroxythiophenol, double-bond functionalized zirconium diboride and N-methylpyrrolidone is 0.26g:1g:10mL. After stirring until uniform, add photoinitiator benzophenone in an amount of 2%-6% of the mass of 4-hydroxythiophenol. Irradiate with an ultraviolet lamp with a wavelength of 365nm and a power of 500W for 20min. Continue stirring to react. After the reaction is completed, filter and collect solid particles, wash three times with alcohol, and vacuum dry to obtain a modified zirconium diboride material.
[0051] The method for preparing the high-strength flame-retardant bus duct comprises the following steps:
[0052] The first step is to weigh epoxy resin, high-strength flame retardant filler, defoamer, and lubricant according to weight parts, mix them evenly, add curing agent, mix them evenly again, and obtain casting resin;
[0053] The second step is to place the busbar in the mold, then pour in the casting resin, vibrate and degas, heat the mold to 150°C for 2 hours, and then naturally cool it and demold it to obtain a high-strength flame-retardant busbar duct.
[0054] Example 3
[0055] A high-strength flame-retardant bus duct comprises a bus and a protective layer arranged on the surface of the bus, wherein the protective layer is prepared by casting resin, and the casting resin is calculated by weight and comprises:
[0056] 100 parts epoxy resin, 42 parts high-strength flame retardant filler, 1 part defoamer, 3 parts lubricant and 40 parts curing agent.
[0057] Wherein, the epoxy resin is epoxy resin E-44, the defoamer is silicone defoamer BYK-141, the lubricant is stearic acid, and the curing agent is anhydride curing agent methyltetrahydrophthalic anhydride.
[0058] Wherein, the preparation method of the modified zirconium diboride material comprises:
[0059] S1. Weigh 600-800 mesh zirconium diboride ceramic powder and anhydrous ethanol, mix them, the mass volume ratio of zirconium diboride ceramic powder and anhydrous ethanol is 1g:20mL, then add vinyl silane coupling agent A-151, the addition amount is 28% of the mass of zirconium diboride ceramic powder, disperse them evenly under the action of ultrasound, then reflux and stir at 70°C for 15h under the protection of nitrogen, after the treatment, filter and collect solid particles, wash them three times with water, and vacuum dry them to obtain double-bond functionalized zirconium diboride;
[0060] S2. Weigh 4-hydroxythiophenol and double-bond functionalized zirconium diboride and add them to N-methylpyrrolidone in sequence. The mass volume ratio of 4-hydroxythiophenol, double-bond functionalized zirconium diboride and N-methylpyrrolidone is 0.52g:1g:20mL. After stirring until uniform, add photoinitiator benzophenone in an amount of 6% of the mass of 4-hydroxythiophenol. Irradiate with an ultraviolet lamp with a wavelength of 365nm and a power of 500W for 60min. Continue stirring to react. After the reaction is completed, filter and collect solid particles, wash three times with alcohol, and vacuum dry to obtain a modified zirconium diboride material.
[0061] The method for preparing the high-strength flame-retardant bus duct comprises the following steps:
[0062] The first step is to weigh epoxy resin, high-strength flame retardant filler, defoamer, and lubricant according to weight parts, mix them evenly, add curing agent, mix them evenly again, and obtain casting resin;
[0063] The second step is to place the busbar in the mold, then pour in the casting resin, vibrate and degas, heat the mold to 130℃ for 4h, and then naturally cool it and demould it to obtain a high-strength flame-retardant busbar duct.
[0064] Comparative Example 1
[0065] A bus duct, the preparation method is the same as that of Example 1, the only difference is that the high-strength flame-retardant filler in the casting resin is replaced with zirconium diboride ceramic powder, and the rest is the same as Example 1.
[0066] Casting resin is calculated by weight and includes:
[0067] 100 parts of epoxy resin, 30 parts of zirconium diboride ceramic powder, 0.6 parts of defoamer, 2 parts of lubricant and 30 parts of curing agent.
[0068] Comparative Example 2
[0069] A bus duct, the preparation method is the same as that of Example 1, the only difference is that the high-strength flame-retardant filler in the casting resin is replaced by double-bond functionalized zirconium diboride, and the rest is the same as that of Example 1.
[0070] Casting resin is calculated by weight and includes:
[0071] 100 parts epoxy resin, 30 parts double bond functionalized zirconium diboride, 0.6 parts defoamer, 2 parts lubricant and 30 parts curing agent.
[0072] The properties of the cured casting resins prepared in Example 1 and Comparative Examples 1-2 were tested. The tensile strength and tensile modulus were tested according to GB / T 2571-1995, the impact strength was tested according to GB / T 2571-1995, and the limiting oxygen index was tested according to GB / T 2406-1993. The test results are shown in Table 1:
[0073] Table 1 Performance test results of different casting resins
[0074] Tensile strength(MPa) Tensile modulus(GPa) <![CDATA[Impact strength (kJ / m 2 )]]> Limiting oxygen index Example 1 98.2 2.3 28.5 31.4 Comparative Example 1 81.5 1.5 19.2 26.2 Comparative Example 2 86.7 1.9 23.7 26.9
[0075] It can be seen from Table 1 that the casting resin of the bus duct prepared in Example 1 has higher strength and toughness, and at the same time has a higher limiting oxygen index, indicating that the flame retardant performance is also stronger.
[0076] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.
[0077] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A high-strength flame-retardant bus duct, characterized in that: It includes a busbar and a protective layer arranged on the surface of the busbar, wherein the protective layer is prepared by casting resin, and the casting resin is calculated by weight and includes: 100 parts of epoxy resin, 18-42 parts of high-strength flame-retardant filler, 0.5-1 parts of defoamer, 1-3 parts of lubricant and 20-40 parts of curing agent; The high-strength flame-retardant filler is a modified zirconium diboride material, which is prepared by chemical click reaction using 4-hydroxythiophenol and double-bond functionalized zirconium diboride as raw materials; The preparation method of the modified zirconium diboride material comprises: S1. Weigh zirconium diboride ceramic powder and anhydrous ethanol, mix them, then add vinyl silane coupling agent, disperse them evenly under the action of ultrasound, and then reflux and stir them under the protection of nitrogen. After the treatment, filter and collect solid particles, wash them three times with water, and vacuum dry them to obtain double-bond functionalized zirconium diboride; S2, weighing 4-hydroxythiophenol and double-bond functionalized zirconium diboride, adding them into N-methylpyrrolidone in sequence, stirring until homogenized, adding a photoinitiator, and continuously stirring the reaction under ultraviolet light. After the reaction is completed, filtering and collecting solid particles, washing with alcohol three times, and vacuum drying to obtain a modified zirconium diboride material; In S1, the particle size of the zirconium diboride ceramic powder is 600-800 mesh; the vinyl silane coupling agent is A-151 or A-172, and the added amount is 16%-28% of the mass of the zirconium diboride ceramic powder; the mass volume ratio of the zirconium diboride ceramic powder and anhydrous ethanol is 1g: (10-20) mL; the treatment temperature is 60-70°C, and the treatment time is 10-15h; In the S2, the mass volume ratio of 4-hydroxythiophenol, double-bond functionalized zirconium diboride, and N-methylpyrrolidone is (0.26-0.52) g:1 g:(10-20) mL.
2. The high-strength flame-retardant bus duct according to claim 1, characterized in that: The epoxy resin is one or more of epoxy resin E-12, epoxy resin E-20, epoxy resin E-44, and epoxy resin E-51.
3. The high-strength flame-retardant bus duct according to claim 1, characterized in that: The defoamer is an organosilicon defoamer, including any one or more of BYK-024, BYK-093, BYK-A530 and BYK-141.
4. The high-strength flame-retardant bus duct according to claim 1, characterized in that: The lubricant is a mixture of one or more of stearic acid, zinc stearate and magnesium stearate.
5. The high-strength flame-retardant bus duct according to claim 1, characterized in that: The curing agent is an acid anhydride curing agent, including a mixture of one or more of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, nadic anhydride, and methylnadic anhydride.
6. The high-strength flame-retardant bus duct according to claim 1, characterized in that: In S2, the photoinitiator is benzophenone, and the added amount is 2%-6% of the mass of 4-hydroxythiophenol; the wavelength of the ultraviolet lamp is 365nm, the power is 500W, and the irradiation time is 20-60min.
7. A method for preparing the high-strength flame-retardant bus duct according to claim 1, characterized in that: The following steps are involved: The first step is to weigh epoxy resin, high-strength flame retardant filler, defoamer, and lubricant according to weight parts, mix them evenly, add curing agent, mix them evenly again, and obtain casting resin; The second step is to place the busbar in the mold, then pour in the casting resin, vibrate and degas, heat the mold to 130-150℃ for 2-4h, and then naturally cool it and demould it to obtain a high-strength flame-retardant busbar duct.